DIMENSI SOSIO-POLITIK KONFLIK AMBON - Didit Rudiansyah (Jurnal Sosiologi Reflektif, 2015)
Conflct is a social aberration (chaos), a state where people are experiencing social disintegration. Conflcts usually occur in people who are going through a transition period. Levels of conflct becomes large if the transition process was also great in all areas (revolution), in contrast to small levels of conflct when the transition process was also small, covering only a few areas only. Driving dimensions can be varied conflcts, be it a political dimension, economic, control over resources, culture, ethnicity and religion. It needs a real resolution as preventive measures (prevention) or curative (repair) in tackling the outbreak of conflct in society.